The efficacy of calcium and vitamin D3 supplementation in improving pregnancy and neonatal outcomes - Wang, Fei; Shen, Mengqing; Wu, Ting; Zhang, Yang; Wang, Yun; Zhou, Congyun (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to evaluate the effects of combined calcium and vitamin D3 supplementation on maternal, pregnancy, and neonatal outcomes.MethodsClinical data from 122 pregnant women were retrospectively analyzed and categorized into three groups based on their actual intake: control (n = 48), Calcium 600-Vitamin D (600 mg calcium + 1,000 IU vitamin D daily, n = 41), and Calcium 1,200-Vitamin D (1,200 mg calcium + 1,000 IU vitamin D daily, n = 33). Baseline characteristics and outcomes including gestational diabetes, preeclampsia, gestational hypertension, birth weight, and Apgar scores were collected and analyzed.ResultsCalcium and vitamin D₃ supplementation was associated with significantly lower rates of gestational diabetes (P = 0.035), preeclampsia (P = 0.032), and gestational hypertension (P = 0.047), as well as reduced leg cramp frequency (P < 0.001). Neonatal outcomes improved with higher birth weights (P < 0.001) and better 1-minute Apgar scores (P < 0.001). Multivariable logistic regression confirmed that high-dose supplementation (Calcium 1,200–Vitamin D) was independently associated with reduced risks of gestational diabetes (OR = 0.423, 95% CI: 0.123–0.869, P = 0.043) and gestational hypertension (OR = 0.342, 95% CI: 0.126–0.875, P = 0.012). Both supplementation groups significantly reduced leg cramp frequency: Calcium 600–Vitamin D (OR = 0.507, 95% CI: 0.355–0.723, P < 0.001) and Calcium 1,200–Vitamin D (OR = 0.512, 95% CI: 0.256–0.985, P = 0.012). No significant differences were found in other outcomes including preterm birth, neonatal infection, or NICU admission (P > 0.05).ConclusionThis study suggests that combined calcium and vitamin D₃ supplementation during pregnancy may help reduce the risk of pregnancy-related complications and improve neonatal outcomes, supporting its potential as an adjunct to prenatal care. Further large-scale and long-term studies are warranted to confirm these findings.